KEBERHASILAN TOILET TRAINING PADA ANAK USIA 2-3 TAHUN DI DUSUN TEGALSARI DESA JABON KECAMATAN MOJOANYAR KABUPATEN MOJOKERTO - Wahyuningrum, Tria; Basuki, Duwi (JURNAL KEPERAWATAN SEHAT, 2016)
Toliet training is a training to puts the activity of defecation and urination in toilet habits in children. The most common impact the failure of toilet training such as the treatment or strict rules for parents to their children, which can interfere with the childs personality, which tends to be retentive (strong), where children tend to be stubborn, even stingy. The purpose of this study is to know, the description of the toilet training fulfillment in children aged 2-3 years in the Tegalsari Hamlet, Jabon Village, District Mojoanyar, Mojokerto. Design of this research using descriptive method. The study population is, all children aged 2-3 years, in the hamlet Tegalsari, Jabon Village, District Mojoanyar, Mojokerto. The research sample as many as 20 children, who were taken using total sampling technique. This research instrument use, sheet checklist, while the method of taking data with observations. Data analysis techniques, using frequency distribution. The result showed, the majority of respondents, children aged 2-3 years, were not able to toilet training, as many as 17 respondents (85%). Observations indicate, there are still many children who have not been able to do, At stage 5, ie cleaning the buttocks (in the hole), or genitals, after completion of the BAB and BAK, using water and tissue, obtained almost all children can not afford, and only 4 children were able to do it yourself, Implementation of toilet training, requiring motor skills of children, both fine motor, and gross motor skills, and the ability to self-reliance. Therefore, mothers should always guide their children, in the use of the toilet, and get children to defecate or urinate using the toilet.Keywords: Toilet Training, Children Aged 2-3 Years